Advanced formulation approaches for ocular drug delivery: state-of-the-art and recent patents - Souto, Eliana B. (2019)
The eye presents extensive perspectives and challenges for drug delivery, mainly because of the extraordinary capacity, intrinsic to this path, for drugs to permeate into the main circulatory system and also for the restrictions of the ocular barriers. Depending on the target segment of the eye, anterior or posterior, the specifications are different. The ocular route experienced in the last decades a lot of progresses related with the development of new drugs, improved formulations, specific-designed delivery and even new routes to administer a drug. Concomitantly, new categories of materials were developed and adapted to encapsulate drugs. With such advances, a multiplicity of parameters became possible to be optimized as the increase in bioavailability and decreased toxic effects of medicines. Also, the formulations were capable to easily adhere to specific tissues, increase the duration of the therapeutic effect and even target the delivery of the treatment. The ascending of new delivery systems for ocular targeting is a current focus, mainly because of the capacity to extend the normal time during which the drug exerts its therapeutic effect and, so, supplying the patients with a product which gives them fewer side effects, fewer number of applications and even more effective outcomes to their pathologies, surpassing the traditionally-used eye drops. Depending on the systems, some are capable of increasing the duration of the drug action as gels, emulsions, prodrugs, liposomes, and ocular inserts with hydrophilic properties, improving the absorption by the cornea. In parallel, other devices use as a strategy the capacity to sustain the release of the carried drugs by means of erodible and non-erodible matrices. This review discusses the different types of advanced formulations used for ocular delivery of therapeutics presenting the most recent patents according to the clinical applications.